Giant cervical cystic hygroma treated with EXIT procedure and bleomycin sclerotherapy - Elaf MohammedHameed Aljifri; Rawan Fahad Bazuhayr; Ruqiah Abdulwahab Alqurashi; Ahdab Hashim Alharbi; Osama A. Bawazir; Alya Alkaff; Hadeel H. Alwadie (Elsevier, 2021)
Introduction: Cystic hygroma are macrocystic benign lymphatic manifestations, developing around 6th gestational week. Treatment options include surgery with associatedcomplications, sclerotherapyusing bleomycin injections. Herein, the case presented was a complicated case of CH. Case: A 31-years-old female, with a history of two previous cesarean-section, was diagnosed with cystic hygroma. A septated cystic lesion was seen in the fetal-MRI, originating at the left lateral neck, below the mastoid bone, down to the level of thoracic inlet, extending to posterior chest wall and crossed the midline. Delivery was performed using EXIT-procedure with head out first to perform intubation. Neonate was successfully treated for CH with tapering doses of Bleomycin injection and a drain inserted for continuous drainage between the injections to avoid fluid re-accumulation. Discussion: A complicated case of CH was completely treated with tapering doses of bleomycin injection. Conclusion: Bleomycin sclerotherapy could serve as future standard management for cystic hygromas.